Effect of economic integration and trade facilitation on Intra-manufacturing export among ECOWAS member states - Adeyinka Olure-Bank; Musthapa Muktar; Ayodeji Salihu; Fadila Kabir Usman (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
Institutional trade tariffs and non-tariff barriers are major constraints to exporters and importers. It affects many developing countries' trade flows and intra-trade performance, including ECOWAS member states. From the classical economic background, the economic problems of international macroeconomics can be examined from the position of trade costs. It further states that low trade facilitation policies such as high tariffs and non-tariff barriers alone can account for a 10% loss in a national income. From these backgrounds, the study assesses the interrelation of economic integration and trade facilitation in ECOWAS and how the member states have performed in intra-manufacturing export. Using the general method of moments (GMM) with instrumental variable (IV) estimation on a dynamic model with panel data from 15 members to analyse how regional economic integration and trade facilitation relationship promote intra-regional manufacturing exports. The findings reveal that trade facilitation in ECOWAS member states is below the world average. Due to high bureaucratic processes, thus, are high costs of exporting/importing. Again, the econometric analyses reveal economic integration significantly promotes trade facilitation in member states and can influence intra-manufacturing exports in ECOWAS. At the same time, manufacturing production has a direct and significant role in manufacturing exports. Some policy recommendations that would help facilitate trade and improve manufacturing production and intra exports in the ECOWAS sub-region were made.